2018
DOI: 10.1590/1806-9061-2017-0672
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cyclic Heat Stress Applied to Different Broiler Chicken Brooding Stages on Animal Performance and Carcass Yield

Abstract: The objective of this study was to evaluate the performance and carcass yield of broilers submitted to heat stress during different rearing stages. A total of 840 one-day-old CobbAvian48 TM male broilers were housed in an experimental house equipped with conventional ventilation system and foggers. Birds were distributed according to a completely randomized design into four treatments, with six replicates of 35 birds each. The treatments consisted of: T1 (control)-birds reared under natural temperature and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Based on these results, we suggest that a larger area available for heat exchange with the environment improves birds' thermal comfort; and birds without feathers on the neck have an increased area to perform this heat loss. It is therefore important to point out that two major points should be considered when analyzing the influence of animal welfare in bird handling: a) feather coverage is related to the bird's accumulation of body heat and its heat exchange with the environment; and b) blood flow is related to the body's heat production (Yahav et al, 2004;Silva et al, 2007;Marchini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, we suggest that a larger area available for heat exchange with the environment improves birds' thermal comfort; and birds without feathers on the neck have an increased area to perform this heat loss. It is therefore important to point out that two major points should be considered when analyzing the influence of animal welfare in bird handling: a) feather coverage is related to the bird's accumulation of body heat and its heat exchange with the environment; and b) blood flow is related to the body's heat production (Yahav et al, 2004;Silva et al, 2007;Marchini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, blood flow is the major responsible for regulating homeostasis processes (Yahav et al, 2001;Yahav et al, 2004;Cangar et al, 2008;Marchini et al, 2018). If the environmental temperature is higher than the body temperature, blood flow tends to decrease in order to reduce the body's heat production.…”
Section: Resultsmentioning
confidence: 99%
“…Heat stress is one of the key environmental factors that affect the growth of broilers ( 36 ). On the other side, Marchini et al ( 37 ) reported that short cycle heat does not impair the performance of the broiler. These findings were supported by the results of the gene expression within the bursa of Fabricius where immune suppression is another disadvantage of temperature modulation ( 38 ), with the results of oxidative stress that emerges from heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Birds are homeothermic organisms having high metabolic activity and no sweat glands. They can tolerate humidity more than high temperatures, and clinical signs of HS develop once the environmental temperature exceeds 30 8C (Marchini et al, 2018). High environmental temperatures alter the activity of the neuroendocrine system in poultry.…”
Section: Introductionmentioning
confidence: 99%